Cancel Culture terhadap Produk yang Dianggap Terafiliasi dengan Israel di Media Sosial X - ZAFIRAMISKA; Febri Nurrahmi (Jurnal InterAct, 2026)
Platform X plays an important role in shaping public opinion and supporting digital activism in mobilizing social movements. However, limited research has examined how digital activism on social media shapes students’ participation in cancel culture. This study aims to understand the dynamics of cancel culture toward against perceived Israel-affiliated products on social media X among students at Syiah Kuala University. The research is grounded in Digital Activism Theory. This study employed a descriptive qualitative method with a phenomenological approach. Data were collected through semi- structured interviews with four students who actively participated in cancel culture practices related to against perceived Israel-affiliated products, supported by documentation in the form of screenshots of digital activities on social media X. The findings show that social media X significantly influences students’ involvement in cancel culture movements against against perceived Israel-affiliated products. Boycott actions have been conducted since 2023 and continue into 2025, with informants demonstrating varying levels of commitment and consistency. Although participation fluctuates, informants consistently express rejection of products affiliated with Israel. Features such as trending topics, tweets, retweets, likes, and shares accelerate information diffusion and strengthen collective awareness, contributing to behavioral changes such as brand switching. Furthermore, students not only engage in cancel culture on X but also disseminate information through WhatsApp and Instagram to broaden the campaign’s reach. The study concludes that cancel culture among students is part of a broader social dynamic that influences consumption behavior, critical awareness, and attitudes toward global humanitarian issues.